Uncovering the Anti-Ebola Repertome - Yamayoshi, Seiya; Kawaoka, Yoshihiro (Cell host & microbe, 2020)
Ebolavirus disease is a global threat. In this issue, Khurana et al. reveal the antibody response against all ebolavirus proteins by analyzing longitudinal antibody repertoires of an Ebola survivor from disease onset. Antibodies against VP40 and GP are found to predominate and two protective antigenic sites in GP identified.